Pengembangan E-Module Berbasis Socio-Scientific Issue pada Materi Sistem Ekskresi untuk Meningkatkan Minat Belajar dan Literasi Sains Siswa Kelas XI - Puspita Mayang Arum Dewantari; Kartika Ratna Pertiwi; Happri Novriza Setya Dhewantoro (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop and evaluate a socio-scientific issues-based e-module to improve eleventh-grade students’ learning interest and scientific literacy on the excretory system topic. The method used was Research and Development employing the ADDIE model, followed by a quasi-experimental design using a pretest-posttest control group design. Data were collected through validation sheets, learning interest questionnaires, and scientific literacy tests. The results showed that the developed e-module had excellent feasibility and practicality based on expert and teacher assessments. In addition, the implementation of the socio-scientific issues-based e-module improved students’ learning interest and scientific literacy better than conventional learning. In conclusion, the socio-scientific issues-based e-module is effective as an innovative learning resource to support meaningful and contextual biology learning. Keywords: E-Module, Learning Interest, Scientific Literacy, Socio-Scientific Issues